Reconciliation: Islam, democracy, and the West - Bhutto, Benazir (Pocket Books, 2008)
Writing a few months prior to her assassination, Bhutto explores the complicated history between the Middle East and the West. She traces the roots of international terrorism across the world, including American support for Pakistani general Zia-ul-Haq, who destroyed political parties, eliminated an independent judiciary, marginalized NGOs, suspended the protection of human rights, and aligned Pakistani intelligence agencies with the most radical elements of the Afghan mujahideen. She speaks out not just to the West, but to the Muslims across the globe who are at a crossroads between the past and the future, between education and ignorance, between peace and terrorism, and between dictatorship and democracy. Democracy and Islam are not incompatible, and the clash between Islam and the West is not inevitable.--From publisher description